Identification of enteropathogenic Escherichia coli as the cause of mastitis in cows from Brazil - Pereira, Erik da S.; Crippa, Bruna L.; Morasi, Rafaela M.; de Almeida, Jaqueline M.; Gebara, Clarice; Langoni, Hélio [UNESP]; Neto, André T.; Gonçalves, Mônica C.; Silva, Nathália Cristina C. (FapUNIFESP (SciELO), 2024)
Pereira E.S., Crippa B.L., Morasi R.M., Almeida J.M., Gebara C., Langoni H., Neto A.T., Gonçalves M.C & Silva N.C.C. 2024. Identification of enteropathogenic Escherichia coli as the cause of mastitis in cows from Brazil. Pesquisa Veterinária Brasileira 44:e07430, 2024. Departamento de Ciência de Alimentos e Nutrição, Faculdade de Engenharia de Alimentos, Universidade Estadual de Campinas, Campinas, SP 13083-862, Brazil. E-mail: ncirone@unicamp.br Escherichia coli is recognized as one of the main microorganisms responsible for triggering clinical mastitis, a disease that causes considerable economic losses in the dairy industry. In this context, this study aimed to identify E. coli isolates present in individual milk samples collected from cows diagnosed with clinical mastitis from various regions of Brazil. Additionally, through polymerase chain reaction (PCR), the presence of virulence genes eae, bfpB, escN, aatA, aggR, ipaH, stx1, stx2, est, and eltA was investigated; all associated with the pathotypes of diarrheagenic Escherichia coli (DEC). As an integral part of the study, a comprehensive assessment of the sensitivity profile of the isolates to 11 different antimicrobials widely used in mastitis treatment was also conducted. A total of 198 milk samples were collected from cows diagnosed with clinical mastitis. Among these samples, 12 isolates (6.07%) demonstrated bacterial growth greater than three Colony-Forming Units (CFU) when grown on MacConkey agar medium and morphological characteristics of E. coli. The disc-diffusion test was used to evaluate the susceptibility of these isolates to antimicrobials, and the most predominant resistance was observed concerning streptomycin and tetracycline, affecting 16.67% of the strains analyzed. Notably, all isolates investigated did not demonstrate the presence of the genes eae, aatA, aggR, ipaH, stx1, stx2, est, and eltA. These results indicate that these isolates do not fit the pathotypes known as diarrheagenic Escherichia coli (DEC). However, one of the isolates tested was positive for the bfpB and escN genes. The detection of resistant E. coli associated with clinical mastitis points to possible gaps in the treatment of the disease. Additionally, the presence of resistance genes in E. coli strains indicates the potential to transmit these genes between animals and, perhaps, along the food chain.
Identificação de Escherichia coli enteropatogênica como causa de mastite em vacas no Brasil
Keywords: antimicrobial resistance; Brazil; clinical mastitis; dairy farms; Escherichia coli